EVALUASI KUALITAS PENGADAAN PETI KEMAS TRUCKING PADA PT XYZ - Shokhifah Amin Nur Rachmah; Nofriani Fajrah (Computer Science and Industrial Engineering, 2024)
The poor quality of containers from trucking companies affected cocoa products and caused customer dissatisfaction and financial losses for PT XYZ, a cocoa product trading company. This research evaluates the quality of container procurement services from trucking companies using the SERVQUAL and Lean Service approach and DPMO and Six Sigma methods. This study also proposes a Self-Assessment Checksheet design based on SAC (Safety, Availability, and Cost) indicators from four standard sources of foodgrade containers. The design was validated and revised by two industry practitioners and one academic. The research results show that service quality has not met the expected standards, indicated by high DPMO values and low Six Sigma levels for all service dimensions, especially Responsiveness and Tangible. The Self-Assessment Checksheet design can help trucking companies improve the quality of their services and achieve better levels of Six Sigma by facilitating them to inspect and assess the quality of the containers they provide. This design is a solution for improvements in the Tangible dimension as the main focus of this research. This study concludes that the Self-Assessment Checksheet design is a useful tool for improving the quality of container procurement services and reducing problems and losses caused by poor quality containers.